Evaluation of cognitive impairment in relapsing-remitting multiple sclerosis patients by using the montreal cognitive assessment test - Hamamci, Mehmet (Annals of Medical Research, 2021)
Aim: Evaluating the cognitive functions of patients with relapsing-remitting multiple sclerosis (RRMS) by using the Montreal Cognitive Assessment (MoCA) Test.Material and Methods: This cross-sectional study consisted of 28 RRMS patients who were diagnosed based on the revised McDonald 2017 criteria and 30 healthy volunteers. The MoCA test and the Expanded Disability Status Scale (EDSS) were applied.Results: The mean age of the RRMS patients was 37.21±5.61, while the mean age of the healthy volunteers was 35.6±10.09 (p=0.459). 17 (60.7%) of the RRMS patients were female, 11 (39.3%) were male, while 16 (63.3%) of the control group were female, and 14 (46.7%) were male (p=0.571). The median total MoCA score was 24 (min: 15, max: 30) for the RRMS patients and 27 (min: 19, max: 30) for the healthy volunteers, and the difference was significant (p=0.006). The scores of the RRMS patients were significantly lower in terms of the MoCA sub-dimensions of executive functions, attention, language and delayed recall. There was a negative, medium-level significant correlation between the total MoCA scores and EDSS scores (r: -0.583; p0.001).Conclusion: The results of this study showed that, in the cognitive dysfunction process in RRMS patients, especially executive functions, attention, language and delayed recall are affected, and there is also a relationship between cognitive dysfunction and disability. Furthermore, these results emphasize the significance of cognitive impairment in RRMS patients and show that the MoCA test may be a practical test that can be used for cognitive monitoring of RRMS patients.Keywords: Orientation; language; memory; learning; attention; cognitive dysfunction.
Keywords: Orientation; language; memory; learning; attention; cognitive dysfunction.